PELAKSANAAN MUTASI PERSONIL KEPOLISIAN DI LINGKUNGAN POLRES KABUPATEN GOWA - Kurniawan, Dwi Rizky; Mone, Ansyari; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of the study was to find out how the implementation of mutation based on the merit system, seniority system, spoil system in the district police. Gowa. This type of research uses a qualitative descriptive type of research.. Data collection technique using interview, observation and documentation methods. Data analysis technique by using data reduction steps, data presentation and the final stage. The results of the study indicate that 1) Meryt Systemcan be interpreted as a mutation process that is very well executed, but has not in accordance with the theory because in the implementation of mutations there are still some employees who don't know the reason for their transfer besides that, there are employees who mutation is not in accordance with the educational background possessed if compared to their position, as well as the presence of employees who have not beenoccupied his position but was transferred to another position, 2) seniority system can be interpreted as a mutation because it affects the level of seniority or because his work experience in the field has been in accordance with what was done because of the mutation of the Gowa Police Police Personnel, it was seen that an employee who wastransfer based on the employee's experience or tenure but usually based on achievements and class rank and it's quite effective, 3) Spoil System In carrying out the mutation of the Gowa Police Police Personnel, it can be said that there is no can be separated from there are still based on kinship considerations. Could It is said that the implementation of this mutation prioritizes individual interests because it involves the basis of likes or dislikes because of proximity to the leaderKeywords: Implementation, Mutation